HUBUNGAN KEMAMPUAN PASSING DENGAN KETEPATAN SHOOTING DALAM PEMBELAJARAN SEPAK BOLA DI KELAS XI SMA NEGERI 1 CIKARANG UTARA - Gemael, Qorry Armen; Kurniawan, Febi; Izzuddin, Deden Akbar (UNIVERSITAS NEGERI MAKASSAR, 2020)
The purpose of this research is to find out the relationship between students' Passing Ability and the level of Accuracy of Soccer Shooting Class XI in North Cikarang High School. In this study, a hypothesis was proposed, namely that there was a significant relationship between students' Passing Ability and the level of Accuracy in Shooting Soccer Class XI in North Cikarang High School,This research uses descriptive method with correlational studies. There is a sampling using a purposive sampling technique, with a total sample of 30 students of class XI in North Cikarang High School. Data collection tools used are: 1). A tool to measure Passing using a passing ability test. 2). Tool for measuring the Accuracy of Shooting Soccer using the Shooting Ball Test to Target. From the calculation of the product moment correlation test obtained by the correlation coefficient value on the relationship between Passing Ability and Football Shooting Accuracyof 0.743. This means that the relationship between the ability to pass with the accuracy of shooting soccer students can be said to be positive.